Vortex Streets on a Sphere - Ghada Alobaidi; Roland Mallier (Journal of Applied Mathematics)
We consider flows on a spherical surface and use a transformation to transport some well-known periodic two-dimensional vortex streets to that spherical surface to arrive at some new expressions for vortex streets on a sphere.